Dynamic interactive theory as a domain-general account of social perception - Freeman, Jonathan B. (Adv Exp Soc Psychol, 2019)
The perception of social categories, emotions, and personality traits from others’ faces each have been studied extensively but in relative isolation. We synthesize emerging findings suggesting that, in each of these domains of social perception, both a variety of bottom-up facial features and top-down social cognitive processes play a part in driving initial perceptions. Among such top-down processes, social-conceptual knowledge in particular can have a fundamental structuring role in how we perceive others’ faces. Extending the Dynamic Interactive framework (Freeman & Ambady, 2011), we outline a perspective whereby the perception of social categories, emotions, and traits from faces can all be conceived as emerging from an integrated system relying on domain-general cognitive properties. Such an account of social perception would envision perceptions to be a rapid, but gradual, process of negotiation between the variety of visual cues inherent to a person and the social cognitive knowledge an individual perceiver brings to the perceptual process. We describe growing evidence in support of this perspective as well as its theoretical implications for social psychology.